(3GdYQGFS aj bUU GdbQBfs - (3CHh ESMGb CMeO Hf eMeO Hf EHQGgje GdfjSGHhQj, GdKYdHj,J (B427 (3g` s ((3CHh ESMGb ESeGYjd Hf jYbhH s)
(3ChdgG (B:s
(3HGH ai PcQ HYV hLhg GdMceI ai JbUjU Gddg JYGdi CNHGQ GdeGVjjf s
(3BNQgG (B:s
(3adeG cai Gddg JYGdi CeQ GUMGH Gdajd YXeJ GdYQH bQjTkG hbGdhG ge Ggd Gddg hGf Gddg YR hLd bGJd Yfge hcaGge hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B212s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1131s
Keywords: (3GdJGQjNs